Gugus Kendali Mutu: Suatu Upaya Meningkatkan Kualitas Output STAIN Jember: Quality Control Circle: An Effort to Improve the Output Quality of the State Islamic College (STAIN) Jember - Ali Saifullah (Fenomena, 2004)
The low quality of graduates from Islamic higher education institutions, particularly STAIN Jember, is a critical issue, evident in some alumni's inability to teach Arabic, read the Qur'an, and pass civil service selection tests. This research addresses the problem map of financial, material, and human resource management, as well as lecturer competence and suboptimal learning systems. The objective is to analyze quality control circles from the perspectives of resource management, lecturer competence, and student learning activities. The study employs a qualitative case study design, collecting data through comprehensive interviews, participant observation, and documentation, and analyzes them descriptively and interpretively using data and method triangulation. Key findings indicate that financial resource management requires greater transparency, infrastructure must be renovated to incorporate technology-based learning media, lecturer competence absolutely needs development, and student learning activities should be directed toward scientific and intellectual patterns. The research concludes that an integrated and sustainable quality control circle is essential, with recommendations for improved management accounting, facility renovation, and the establishment of cross-departmental scientific forums and literary study groups. Fenomena rendahnya kualitas lulusan perguruan tinggi agama, khususnya STAIN Jember, menjadi isu krusial yang tercermin dari ketidakmampuan sebagian alumni dalam mengajar bahasa Arab, membaca Al-Qur'an, serta lulus ujian Calon Pegawai Negeri Sipil. Penelitian ini bertolak dari peta masalah pengelolaan sumber daya finansial, material, dan manusia, serta kompetensi dosen dan sistem pembelajaran yang belum optimal. Tujuan penelitian adalah menganalisis gugus kendali mutu dalam perspektif pengelolaan sumber daya, kompetensi dosen, dan aktivitas belajar mahasiswa. Penelitian menggunakan metodologi kualitatif dengan rancangan studi kasus, pengumpulan data melalui wawancara komprehensif, observasi partisipan, dan dokumentasi, serta dianalisis secara deskriptif interpretatif dengan triangulasi data dan metode. Temuan utama menunjukkan bahwa pengelolaan sumber daya finansial perlu peningkatan transparansi, sarana prasarana harus direnovasi berbasis teknologi, kompetensi dosen mutlak dikembangkan, serta aktivitas belajar mahasiswa perlu diarahkan pada pola ilmiah dan intelektual. Penelitian menyimpulkan bahwa gugus kendali mutu yang terpadu dan berkelanjutan sangat diperlukan, dengan rekomendasi peningkatan manajemen akuntansi, renovasi fasilitas, serta pembentukan forum kajian ilmiah dan kepustakaan lintas jurusan.